The Use of Indocyanine Green Angiography for Cosmetic and Reconstructive Assessment in the Head and Neck - Abdelwahab, Mohamed; Patel, Priyesh N.; Most, Sam P. (Facial Plastic Surgery, 2020)
Reconstructive procedures in the head and neck can be a surgical challenge owing to the complex anatomical and physiological structure. Different locoregional and microvascular flaps are used for various defects to improve both function and cosmesis. Subjective clinical findings have been the mainstay for perfusion monitoring; however, areas of borderline perfusion are much more difficult to assess clinically. Multiple technologies that offer objective perfusion assessment have been developed to improve surgical outcomes. Indocyanine green (ICG) angiography has gained popularity owing to its minimal invasiveness and increased sensitivity and specificity in assessing flap perfusion particularly in the head and neck. It has been extensively used in free flaps, pedicled flaps (including nasal reconstruction), facelift procedures, random flaps, skull base reconstruction, and pharyngocutaneous fistula prediction. Its perioperative use has provided valuable qualitative and quantitative data that aid our understanding of flap hemodynamics. Clinically, this impacted decision-making in flap design, harvest, inset, and precocious salvage interventions. Though increased cost and intraoperative time could be limitations, cost-effectiveness studies have supported its use, particularly in high-risk individuals. Limitations include the lack of standardized dosing and consistent methodology agreement for data analysis. Future studies should involve larger cohorts and multi-institute studies to overcome such limitations.
Keywords: indocyanine green; fluorescence; angiography; head and neck; reconstruction; free flap; facelift; nasal reconstruction; facial plastic surgery